Groundwater development for agriculture in eastern India: Problems, prospects, and issues - Prasad, T.; Sharma, I. D. (International Food Policy Research Institute, 1990)
Eastern India had been a region of iffluence and the center of Indian prosperity for long periods ii history. After almost uninterrupted progress and prosperity, a gray period in its history seems to have set in about 1200 A.D. The process of gradual decline began to manifest itself in stresses ir the lives of individuals, administrative and political upheavals, ind associated phenomena in the late 17th century. The declining conditions in eastern India influenced the course of history of the country: the downfall of the Moghul Empire, the advent of British rule, and the mass struggle for freedom.